Influence of Emotional Intelligence on the Mental Health of the Federal Road Safety Corps Personnel in Benue State Sector Command - Zakariah, Danladi; Ihaji, Elvis O.; Akafa, Tensaba Andes; Akafa, Vika Tensaba; Iseko, Kingsley Iyoko; Oladele, Gloria Omonefe (Darul Yasin Al Sys, 2024)
This study examined Emotional Intelligence on the Mental Health of the Federal Road Safety Corps Personnel in Benue State Sector Command. The study employed a cross-sectional survey design in which 232 Federal Road Safety Corps Personnel whose ages ranged from 20 – 58 years (Mean age=36.30, SD=8.34), comprising 169(72.8%) males and 63(27.2%) females who served as participants for the study. Emotional intelligence Scale and Mental Health Inventory scale were used in data collection. The result of the finding shows that, there was a significant positive influence of emotional intelligence on mental health of Federal Road Safety Corps Personnel in Benue State Sector Command [R=.436, R2=.190, F (5,227) =3.627, p<.01]. The result also indicated that, emotional intelligence and its dimensions explained 19.0% of the variance observed in mental health among the participants. This means that, Federal Road Safety Personnel with high levels of emotional intelligence are likely to have good mental health, and the extent to which emotional intelligence explains mental health of Federal Road Safety Corps Personnel in Benue State Sector Command is 19.0%, and based on this finding, the second hypothesis was confirmed. Independently, findings revealed that, social skills made the highest significant contribution (β=.299, t=2.988, p<.05), followed by motivation (β=.223, t=2.588, p<.05), and then self-reputation (β=.211, t=2.081, p<.05), followed by social awareness (β=.198, t=1.758, p<.05), and self-awareness (β=.180, t=1.313, p<.05) successively. Based on this finding, it was recommended that the management of Federal Road Safety Corps in Benue State Sector should explore ways of improving the personnel's emotional intelligence deficit which may enhance succees and improve their mental health.